INSIGHTS INTO ETHICAL PERCEPTION IN ACCOUNTING EDUCATION - Diana-Elisabeta MATICA; Edi-Cristian DUMITRA; Dana LUPU (CONSTANTINICA) (Annals of the University of Oradea: Economic Science)
Recently, ethics has become increasingly central in higher education, with more and more researchers and educators focusing on its integration into curricula and academic practice. The renewed attention to ethical aspects in accounting is evident, with notable references to past scandals such as Enron, WorldCom, and Tyco, highlighting the risks of unethical behaviour. Client pressure to present a positive financial image can sometimes lead to breaches of ethical standards, underscoring the need for ongoing education and awareness in this field. The present quantitative investigation is grounded in empirical analysis and scrutinizes the perspectives of both master's and bachelor's students in accounting regarding business ethics and the aims of ethics education in accounting. To assess students' viewpoints concerning the significance of business ethics and education in accounting ethics, we use Likert scale and employ an exploratory factor analysis on data collected through a questionnaire-based survey (a replication of the one conducted by Adkins and Radtke, 2004) distributed among both bachelor's and master's accounting students at one of the universities in Romania, namely The Faculty of Economics from University of Oradea (FSE). Our results, based on statistical analyses, indicate that master's and bachelor's students exhibit consistent views on the importance of ethics courses in accounting, regardless of their completed accounting courses.